Ratio-dependent functional response of two common Cladocera present in farmland ponds to Batrachochytrium dendrobatidis. (October 2021) - De Troyer, Niels; Bruneel, Stijn; Lock, Koen; Greener, Mark S.; Facq, Ennio; Deknock, Arne; Martel, An; Pasmans, Frank; Goethals, Peter
Abstract: Batrachochytrium dendrobatidis is responsible for amphibian declines worldwide. Decreasing the aquatic density of this chytrid through consumption of its infectious zoospores by Cladocera (water fleas) may mitigate the impact of chytridiomycosis. Understanding this predator-prey relationship requires insights in the zoospore ingestion rate of an average water flea, but such data are almost non-existent. We investigated the functional response of Simocephalus vetulus and Chydorus sphaericus feeding on B. dendrobatidis zoospores. These Cladocera commonly occur in farmland ponds, which may represent a major habitat for disease control. Both water fleas actively ingested zoospores and their per capita ingestion rate was best modelled in function of zoospore-to-Cladocera ratio, implying mutual interference among water fleas during zoospore feeding. The larger S. vetulus substantially consumed more zoospores, characterised by a maximum ingestion rate of 2.5 × 10 5 zoospores.Cladocera −1 .h −1 .mL −1, which is about 12 times higher than for C. sphaericus . These findings are useful to support model-based management of chytridiomycosis. Highlights: Simocephalus vetulus and Chydorus sphaericus are common Cladocera in farmland ponds. S. vetulus and C. sphaericus consume zoospores of B. dendrobatidis . Zoospore ingestion rate for both Cladocera depends on zoospore-to-Cladocera ratio. The larger S. vetulus has a significant larger per capita ingestion rate than C. sphaericus .